2022
DOI: 10.3389/fpsyg.2022.955300
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership and flourishing: Do trust in the organization and organizational support matter during times of uncertainty?

Abstract: Orientation: This study investigated the influence of authentic leadership on employee flourishing while considering the potential mediating effect of trust in the organization and organizational support as underlying mechanisms in an uncertain setting.Research purpose: To examine the relationship between authentic leadership and employee flourishing by evaluating the indirect effect of organizational support and trust in the organization as potential mediators.Motivation for the study: An authentic leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 155 publications
0
0
0
Order By: Relevance
“…Eisenberger and colleagues (2020) argue that supportive leaders—i.e., who treat their followers fairly, show concern for them, and coach them—may increase followers’ POS, which in turn enhances WE. Previous research has demonstrated that POS mediates the relationship between positive leadership behaviors (e.g., transformational leadership, authentic leadership, and ethical leadership) and employee outcomes (Kim & Vandenberghe, 2021; Kleynhans et al, 2022; Stinglhamber et al, 2015).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Eisenberger and colleagues (2020) argue that supportive leaders—i.e., who treat their followers fairly, show concern for them, and coach them—may increase followers’ POS, which in turn enhances WE. Previous research has demonstrated that POS mediates the relationship between positive leadership behaviors (e.g., transformational leadership, authentic leadership, and ethical leadership) and employee outcomes (Kim & Vandenberghe, 2021; Kleynhans et al, 2022; Stinglhamber et al, 2015).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Given that employees have a close relationship with management, employees naturally work hard to feel valued and to earn a raise, just as social exchange theory suggests. However, hard-working employees who are scolded or mistreated by their supervisors will be less motivated and make less effort to ensure fairness in social exchange [18,19]. Understanding factors that relate to satisfaction with supervisor leadership from the perspective of nurses is crucial for supervisors.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, numerous studies have found that authentic leadership is correlated with increased individual satisfaction with management, organisational commitment, additional effort, and institutional framing perception. The perception of authentic leadership not only positively affects an individual's institutional framing perceptions and happiness, but it can also-at least indirectly-have a positive impact on the performance of any organisation, taking into account the positive relationship between institutional framing perception and performance results such as productivity, benefits, or client satisfaction (Kleynhans et al, 2022). Jiang (2020) focused on leadership style and how leaders at Nanking Normal University's (NNU) School of Education Science (SES) carry out their leadership study.…”
Section: Introductionmentioning
confidence: 99%